2006
DOI: 10.1128/jcm.01506-06
|View full text |Cite
|
Sign up to set email alerts
|

Use of Smear-Positive Samples To Assess the PCR-Based Genotype MTBDR Assay for Rapid, Direct Detection of the Mycobacterium tuberculosis Complex as Well as Its Resistance to Isoniazid and Rifampin

Abstract: Isoniazid (INH) and rifampin (RIF) are two of the most important antituberculosis drugs, and resistance to both of these drugs can often result in treatment failure and fatal clinical outcome. Resistance to these two first-line drugs is most often attributed to mutations in the katG, inhA, and rpoB genes. Historically, the identification and testing of the susceptibility of Mycobacterium tuberculosis complex (MTBC) strains takes weeks to complete. Rapid detection of resistance using the PCR-based Genotype MTBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 20 publications
4
40
1
Order By: Relevance
“…This is in agreement with the high sensitivity reported elsewhere [30,31,32]. However, the results for detection of resistance to INH were much lower using this assay.…”
Section: Profiles Of Drug Susceptibility Patterns Of Mycobacterium Tusupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with the high sensitivity reported elsewhere [30,31,32]. However, the results for detection of resistance to INH were much lower using this assay.…”
Section: Profiles Of Drug Susceptibility Patterns Of Mycobacterium Tusupporting
confidence: 92%
“…In this study, only 34.6% resistance to INH was detected using the MTBDRplus assay which is less than that reported by Johnson et al, 2008 [36]. Other studies showed detection of 60-90% within the katG gene and 15-43% within the inhA gene [32,31]. Nonetheless, it must be kept in mind that the isolates used in this study were screened using the single drug concentration of 0.1μg/ml of INH in the BACTEC 460 TB system (which detects low levels of resistance to INH at this concentration, mainly useful for therapeutic purposes).…”
Section: Profiles Of Drug Susceptibility Patterns Of Mycobacterium Tucontrasting
confidence: 79%
“…Another study, which tested the GT assay directly in 42 smear-positive sputum specimens, found 100% concordance with conventional drug susceptibility testing [28]. In a study where the GT assay was directly used in 143 smear-positive specimens, a sensitivity of 94% for katG and 91% for rpoB was achieved and the assay correctly identified INH resistance in 84% of specimens with high-level INH resistance and 96% of specimens with RIF resistance [29]. Recently, studies on the new extended GTplus assay have found, similarly to our findings, that it could be applied directly in smear-positive specimens [30,31].…”
Section: Discussionmentioning
confidence: 97%
“…If the type of mutation is not known to the laboratory scientist or the clinician, it is not possible to draw meaningful conclusions for designing an appropriate drug regimen. In addition, it is clear that some of these less common mutations, which may reach 22% of all RIF-resistant cases in certain areas (14,15), are associated with a phenotypic RIF resistance of Ͻ1.0 g/ml, which is also the definition criteria for MDR-TB. Preliminary results indicate that patients with such mutant strains may fail more often under firstline therapy with standard RIF doses (13).…”
Section: (Ii) Is It Important To Have Information On the Type Mutatiomentioning
confidence: 99%